Banditry in Semarang, 1950-1958 - Joseph Army Sadhyoko; Agustinus Supriyono; Dhanang Respati Puguh (Diponegoro University, 2017)
This article discusses about banditry that occurred in Semarang during the period of 1950-1958 with the problem focus on the causes of the banditry, types of banditry, and mitigation. Through the historical method, this article reconstructs those problems by using the approach of social reality of crime concept. In result, the banditry happened in the aftermath of the independence war, occurred due to economic difficulties, the reorganization and rationalization program, and the circulation of guns that was uncontrolled.